RESPONSE OF LOCAL GRASS TO THE PROVISION OF VARIOUS DOSAGE OF UREA FERTILIZER - A., Rifais; Trisnadewi, A. A. A. S.; Wirawan, I W. (Jurnal Peternakan Tropika, 2018)
This study aimed to obtain information the response of grass Leersia hexandra Sw, Heteropogon contortus , and Chloris barbata at various dosage of urea and its interactions. This research was conducted at greenhouse in Sading Village, Mengwi Sub-district, Badung Regency, Bali. The study lasted for 10 weeks, using completely randomized design (CDR) split plot pattern consists of three main plot grass of Leersia hexandra sw , Heteropogon contortus , and Chloris barbata, then four subplots / subplots consist of urea fertilizer various dosages of 0 kg/ha (D0), 50 kg/ha (D1), 100 kg/ha (D2) and 150 kg/ha (D3) so there are 12 treatment combinations repeated four time so that there where 48 unit experiment. Variables observed were growth, production and characteristics plants. Results of the research significant interaction between the grass kind and fertilizer dosage to leaf area variable. HD3 treatment combination gives the highest while LD0 treatment combination gives the lowest of growth and production of local grass and urea fertilizer dosage. Showed kind of local grass significantly effect to leaf of number, tiller of number, leaf dry weight, stem dry weight, all forage dry weight, all forage dry wight with root dry weight and leaf area. The provision of urea fertilizer was significant effect to all variables except for plant height, root dry weight and dry weight of leaf ratio with stems ratio.Based on the result of research it can be concluded that there was local grass Heteropogon contortus give the best result compared to the type off grass Leersia hexandra Sw and Chloris barbata in fertilazition urea. Urea fertilizer dosage 150 kg/ha give the best response of local grass. There was a significant interaction between the grass type and the fertilizer dosage leaf area.   Keywords: local grass, urea, dosage, growth, production